The New Chinese Traveler Business Opportunities from the Chinese Travel Revolution - Bowerman, G.; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2014)
This book explains the emerging trends and developments of Chinese outbound travel, alongside the motivations, desires and expectations of Chinese travelers themselves. Packed with interviews, this book will help businesses create products and services that meet the rapidly evolving and diversifying requirements of tech-savvy Chinese travelers.
Keywords: Ethnology—Asia.; Business; Management science; Leadership; Tourism; Management; Trade; Commerce; Economics; Asian Culture; Business and Management, general; Business Strategy/Leadership.; Tourism Management; Trade; Economics, general